Safe administration of docetaxel after weekly paclitaxel-induced acute pancreatitis. (October 2017) - Adam, Jean-Philippe; Gauthier, Philippe; Letarte, Nathalie
Acute pancreatitis is an inflammatory process of the pancreas that can be mild to severe. It requires biochemical or radiologic evidence to establish the diagnosis. Only few chemotherapy agents are directly linked to acute pancreatitis. In this case report, we describe a patient who developed a mild acute pancreatitis on weekly paclitaxel with a positive dechallenge and rechallenge. A 57-year-old woman with advanced ovarian cancer started chemotherapy with carboplatin (AUC 5 every three weeks) and weekly paclitaxel (80 mg/m 2 on days 1, 8, and 15). On day 13 of cycle 1, the patient presented with elevated lipase and mild epigastric pain with a suspicion of acute pancreatitis. Because the patient was asymptomatic and pancreatic enzymes decreased on day 16, the third paclitaxel dose was given on day 17 and was followed by another increase of these enzymes. She later received carboplatin and docetaxel without any perturbation of the amylase and lipase. Applying the Naranjo adverse drug reaction probability scale, a score of nine was obtained, indicating a definite association between the administration of paclitaxel and acute pancreatitis. This adverse event could be explained by paclitaxel itself or one of two diluents: cremophor or ethanol. Because paclitaxel is use in many chemotherapy protocols, pharmacists and physicians should be aware of this rare adverse event. Docetaxel administration proved to be safe in this patient without any appearance of pancreatitis signs or symptoms.